Analisis Pemborosan Pada Area Penyimpanan Di Gudang Sparepart Dengan Metode Waste Assesment Model - Fawwazdiq, Althaf Dientsany; Sutrisno, Sutrisno (Fakultas Teknik Universitas Tulang Bawang, 2024)
The Material Department at PT Pupuk Kujang faces significant challenges in spare part storage, including stockpiling, excess materials, and unused items. To address these issues efficiently, identifying critical waste, the most dominant and urgently requiring improvement, is crucial. The Waste Assessment Model (WAM) is a suitable method for this purpose. The waste identification process involves using the Seven Waste Relationship (SWR), Waste Relationship Matrix (WRM), and Waste Assessment Questionnaire (WAQ). Root cause analysis is then conducted with a Fishbone Diagram for prompt improvements. Research results reveal the following waste rankings: Overproduction at 20.27%, Inventory at 18.60%, Motion at 16.33%, Defect at 14.94%, Transportation at 14.29%, Waiting at 9.73%, and Process at 5.83%. The two largest percentages, Overproduction and Inventory, are critical wastes. This classification enables root cause determination using the Fishbone Diagram and provides recommendations for waste reduction Keywords: Fishbone Diagram, Lean Manufacturing, Waste, Waste Assessment Mode